2006
DOI: 10.1007/s10822-006-9038-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of substituent effect of 1-(3,3-diphenylpropyl)-piperidinyl phenylacetamides on CCR5 binding affinity using QSAR and virtual screening techniques

Abstract: SummaryA linear quantitative-structure activity relationship model is developed in this work using Multiple Linear Regression Analysis as applied to a series of 51 1-(3,3-diphenylpropyl)-piperidinyl phenylacetamides derivatives with CCR5 binding affinity. For the selection of the best variables the Elimination SelectionStepwise Regression Method (ES-SWR) is utilized. The predictive ability of the model is evaluated against a set of 13 compounds. Based on the produced QSAR model and an analysis on the domain of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…This test ensures the robustness of a QSAR model [19] and to assess the multiple linear regression models obtained by descriptor selection [20]. In y-randomization test, the dependent variable or y-data is randomly shuffled and a new QSAR model is developed keeping X-data intact.…”
Section: Y-randomizationmentioning
confidence: 99%
“…This test ensures the robustness of a QSAR model [19] and to assess the multiple linear regression models obtained by descriptor selection [20]. In y-randomization test, the dependent variable or y-data is randomly shuffled and a new QSAR model is developed keeping X-data intact.…”
Section: Y-randomizationmentioning
confidence: 99%
“…Aiming at overcoming the inherent limitations, the integration of VS and QSAR strategies provides useful opportunities to partially fulfill each method limitation, as well as allows the capture and incorporation of valuable information for the design of new small-molecule drug candidates. A variety of studies describing the integration of these drug design techniques has been reported in the literature [91][92][93][94][95][96]. For example, investigations were conducted for the discovery of inhibitors of 3-hydroxy-3-methyl-glutaryl-CoA reductase (HMGR) [91], through the integration of 3D QSAR CoMFA (Comparative Molecular Field Analysis) models [97] and FlexE [98] pre-filters based on energy score.…”
Section: Integrating Vs and Qsarmentioning
confidence: 99%
“…In this approach, QSAR models would be capable of identifying most probable nonbinders in docking databases, and also be used together with other pre-docking filters. Similarly, MLR (Multiple Linear Regression) models were developed for a series of chemokine receptor (CCR5) modulators, in order to create a useful alternative to filter out dissimilar compounds and to identify novel potent compounds [94].…”
Section: Integrating Vs and Qsarmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature survey showed that previously 3D-QSAR and virtual screening studies of CCR5 antagonists 1-(3,3-diphenyl- 18,19 They shows that for high affinity binders key chemical and structural requirement can be identified using physicochemical parameter, topological property and 3D field such as steric, electrostatics, hydrophobic, hydrogen bond donor/acceptor around a set of aligned ligand molecules. 3D-QSAR models, CoMFA and CoMSIA on a series of piperidine-based CCR5 antagonists have been developed by Song et al 20 Whereas, Y. Zhuo et al performed 3D-QSAR study for 1,3,4-trisubstituted pyrrolidine based CCR5 inhibitors.…”
Section: Introductionmentioning
confidence: 99%